ANALISIS MUTU STRUKTUR BETON BERTULANG PROYEK PEMBANGUNAN X-CHANGE MALL 2 - Dandi Laksamana; Ayu Herzanita; Imam Hagni Puspito (Construction and Material Journal, 2022)
Every construction is expected to run well and will be completed in accordance with the planning. Therefore, project quality control is needed. Project quality control is extremely useful for one-time development so that the building can achieve its predetermined quality and standards. The purpose of this study is to find out the quality control system of reinforced concrete of upper structures on Columns, Beams, and Plates and whether the quality results of the reinforced concrete structure can meet the specified requirements. The data used in this study were the results of concrete compressive strength tests and steel reinforcement tests that had been carried out in the laboratory. This research was needed to minimize delays and costs so as not to miss the predetermined quality and standards. This research used the AS/NZS 4360 calculation method in which the analysis was carried out by taking into account the level of risk of the probability that occurs and the impact on costs, where the quality applied must be in accordance with the RKS that has been set on the project, the calculation was carried out using Excel in accordance with the formula to determine the level of risk in each structural work. The data were collected by distributing the questionnaire to each individual where the questionnaire contained work items to be analyzed from the division. The calculation analysis has obtained the result of the risk level for each structural work, column work worth 5.20, beam work 5.97 and floor plate work worth 6.00 which means that the work of the structure has a moderate level of risk. Keywords: Quality Control, Construction Implementation, Risk Factors, AS/NZS 4360.